PENGARUH WAKTU AGING TERHADAP SIFAT HIDROFOBISITAS SILIKA XEROGEL TERMOFIDIFIKASI TRIMETILKLOROSILAN (EFFECT OF AGING TIME ON THE HYDROPHOBICITY OF SYNTHESIZED TRIMETHYLCHLOROSILANE-MODIFIED SILICA XEROGE) - Pendi Wahyudi; Andi Hairil Alimuddin; Anis Shofiyani (Tanjungpura University, 2020)
Silica xerogel is a multi-functional material that is useful in many industrial applications. In this research, we synthesized surface-modified silica xerogel and studied the effect of aging time, i.e., 0, 3, 6, 12, and 18 hours to the hydrophobicity of the synthesized material. The synthesis was conducted by the sol-gel method using sodium silicate precursors and a citric acid catalyst. Meanwhile, the surface modification was carried out through the silylation reaction using trimethylchlorosilane (TMCS) reagent. The resulting materials were characterized using infrared spectrophotometry (FTIR) and X-ray diffraction (XRD) methods. Hydrophobicity was measured by the contact angle formed by the water droplet with the xerogel surface and the spreading time of the droplet to be dispersed entirely on the surface. The silica xerogel produced at all aging time variations has an amorphous phase, characterized by 2θ = 22-26o of the XRD pattern. Si-CH3 and C-H vibrations at 848 cm-1 and 2962 cm-1 present in the FTIR spectrumconfirm the success of surface modification. The increasing aging time enhances the contact angle and spreading time of water droplets on xerogels, viz., 130o to 135o,and 3h 10min to 3h 28 min, respectively. Thus, the xerogels produced by this research are hydrophobic.